(untitled) (Colombia Medica, 2022)
Talking about good death is a significant commitment. From clinical practice, it is possible to have a distant view, highly focused on the biological domains of the process, but unquestionably the most accurate and complete vision is the one that unites the biological component with the human component; that is, as part of a process that will also be part of my existence. Whenever we reflect on our death or that of a loved one, our innate desire emerges for this moment to be free of unnecessary suffering, recognizing this as a fundamental right for any human being. Moreover, this right will always be governed by the dignity of the human being; dignity is the basic framework that supports this desire.